SKENARIO PENGENDALIAN BANJIR KAWASAN OPI JAKABARING MASA KINI DAN AKAN DATANG - Muallimah Gustini; Robiyanto H. Susanto; Edward Saleh (INFO-TEKNIK, 2015)
In the interests of regional development, regional development and improvement of the economy has made many changes and conversion of areas in South Sumatra. Over this function especially for the area as the capital of Palembang, South Sumatra Province occur in lowland areas, especially wetlands. Regions that experienced the greatest change in Palembang, namely in the area of Jakabaring. Jakabaring area converted into international sports facilities Jakabaring Sport Center, athlete housing, shops, offices, recreation and pemukimanan population such as housing Ogan Permata Indah (OPI). This marsh land conversion has consequences for water infiltration and runoff water in wetlands, it is necessary to balance the OPI retention pond soil conditions of the region.For that conducted the study in order to obtain the determination of flood control and inundation scenarios in the study site of the present and future. Keywords: transformation of the land area of wetlands, flood control and inundation.